Diagnosis of Mycobacterium tuberculosis Septic Shock in Patients With Anti-synthetase Syndrome Based on Next-Generation Sequencing: A Case Report and Literature Review - Sun, Limin; Yang, Ziyue; Yang, Fei; Wang, Zhenhua; Li, Hongqiang; Wang, Huifen; Sun, Tongwen (Frontiers in Medicine, 2021)
A 51-year-old woman was transferred to the intensive care unit with such symptoms as fever, swollen left knee joint, pain and hypotension. After preliminary evaluation, she was diagnosed as suffering acute suppurative arthritis and septic shock. Then, she was rescued and prescribed to receive treatment with broad-spectrum antibiotics. However, there was no source of infection identified except for the knee joint. The bacterial and fungal cultures of blood samples and articular effusion were shown to be negative, while the results obtained from the next-generation sequencing of blood and articular effusion revealed that Mycobacterium tuberculosis was positive. The patient was then put on five combinations of anti-tuberculosis therapeutic treatment. Nevertheless, despite the active anti-tuberculosis treatment put in place, her general condition still deteriorated progressively. As the level of her bilirubin continued to rise, further treatment was affected, which prompted the change made to the anti-tuberculosis treatment program. Her clinical condition continued to deteriorate, which led to the development of unstable vital signs and the multiple organ dysfunction syndrome. In spite of our best efforts to save her life, the patient still ended up with death.